The value of moderation in the context of national unity in Malaysia - Mohamad Zaidin, Mat@Mohamad; Zulkifli, Mohd; Wan Mohd Yusof, Wan Chik (Medwell Journals, 2014)
A country with a pluralistic society like Malaysia constantly faces issues on unity and racial harmony which becomes increasingly complex from time to time. A conscientious society and the monitoring by the government of interracial relations are needed to safeguard and maintain the nation's stability. This study intends to identify strategies that reinforce the value of unity among the people of Malaysia which is pivoted on the understanding of historical values and the present reality that exist in the country.